2022
DOI: 10.1186/s12964-022-00983-4
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF upregulates StAR expression and stimulates progesterone production through ERK1/2 signaling in human granulosa-lutein cells

Abstract: Background Heparin-binding epidermal growth factor-like growth factor (HB-EGF) belongs to the epidermal growth factor (EGF) family of growth factors. HB-EGF and its receptors, epidermal growth factor receptor (EGFR) and HER4, are expressed in the human corpus luteum. HB-EGF has been shown to regulate luteal function by preventing cell apoptosis. Steroidogenesis is the primary function of the human corpus luteum. Steroidogenic acute regulatory protein (StAR) plays a critical role in steroidogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…As shown in Fig. 4C and D , due to the off-target effect, pretreatment with U0126 increased the basal protein levels of StAR, which is consistent with our previous study [ 26 ]. However, inhibition of ERK1/2 signaling blocked the RSV-induced upregulation of StAR protein levels in both KGN and primary hGL cells.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Fig. 4C and D , due to the off-target effect, pretreatment with U0126 increased the basal protein levels of StAR, which is consistent with our previous study [ 26 ]. However, inhibition of ERK1/2 signaling blocked the RSV-induced upregulation of StAR protein levels in both KGN and primary hGL cells.…”
Section: Resultssupporting
confidence: 92%
“…HB-EGF then binds and activates EGFR leading to downstream activation of signaling molecules, such as ERK1/2 [ 35 , 36 ]. Our recent study demonstrates that HB-EGF induces upregulation of StAR expression and P4 production in both KGN and primary hGL cells and these effects require the EGFR-mediated activation of the ERK1/2 signaling pathway [ 26 ]. In the present study, our results showed that activation of ERK1/2 signaling was involved in RSV-stimulated StAR expression and P4 production in both KGN and primary hGL cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have revealed inhibition of the ERK pathway and reduced HB-EGF levels in PCOS patients (188). Expression of StAR and subsequently increased progesterone synthesis could be modulated by upregulation of ERK activity (189,190). A series of studies have demonstrated that administration of an NK3R antagonist (fezolinetant) leads to a reduction in LH secretion and attenuates symptoms of PCOS by reducing GnRH pulse generation (191).…”
Section: The Mapk Pathwaymentioning
confidence: 99%
“…The evolution of the corpus luteum includes development, maintenance, and degradation, which are essential for maintaining a normal menstrual cycle, regulating the development of follicles, promoting the implantation of embryos, and protecting the safety of early pregnancy [ 3 , 4 ]. Dysfunction of the corpus luteum is involved in some diseases of the corpus luteum such as corpus luteum rupture and luteal phase deficiency [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%